2011
DOI: 10.3897/zookeys.150.2149
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the broader community in biodiversity research: the concept of the COMBER pilot project for divers in ViBRANT

Abstract: This paper discusses the design and implementation of a citizen science pilot project, COMBER (Citizens’ Network for the Observation of Marine BiodivERsity, http://www.comber.hcmr.gr), which has been initiated under the ViBRANT EU e-infrastructure. It is designed and implemented for divers and snorkelers who are interested in participating in marine biodiversity citizen science projects. It shows the necessity of engaging the broader community in the marine biodiversity monitoring and research projects, networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Published citizen science projects on water quality were less frequent and commonly focused on freshwater ecosystems, although studies of coastal marine ecosystems were reported (Arvanitidis et al 2011). Freshwater studies are facilitated by their common presence in most population centers.…”
Section: Characterization Of the Publications From The Databasementioning
confidence: 99%
“…Published citizen science projects on water quality were less frequent and commonly focused on freshwater ecosystems, although studies of coastal marine ecosystems were reported (Arvanitidis et al 2011). Freshwater studies are facilitated by their common presence in most population centers.…”
Section: Characterization Of the Publications From The Databasementioning
confidence: 99%
“…However, data assembled by non-experts should go through quality control before being used in scientific analyses or reposited to global biodiversity databases (Arvanitidis et al 2011, Thiel et al 2014). The list of organisms included in the present CS protocol include conspicuous species that are relatively easy to correctly identify.…”
Section: Discussionmentioning
confidence: 99%
“…Past experience from CS projects showed that it is relatively easy to design a CS approach and address volunteers but hard to ensure continuous production and flow of useful and reliable data (Arvanitidis et al 2011). In retrospect, a key aspect in the design of this pilot project was the collection of data that are: (a) relatively easy to acquire and report, based on the overall, underlying principle "keep it as simple as possible", and (b) reliable and fail-proof.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arvanitidis et al. 2011); or reporting the discovery of new species as a result of citizen science (e.g. Collins et al.…”
Section: The Emergence Of Citizen Sciencementioning
confidence: 99%